(untitled) (Bangladesh Journal of Medical Science, 2026)
Background A supportive educational environment (EE) is essential for effective learning and professional development among health sciences students. This study aimed to evaluate the students’ perceptions of medical, nursing, and pharmacy programs regarding their EE at Widad University College (WUC) and to explore the relationship between perceptions at programs and year-levels. Methods A cross-sectional study was conducted in 2025 involving 165 undergraduate students across medicine, nursing, and pharmacy programs. The 50-item Dundee Ready Education Environment Measure (DREEM) questionnaire assessed perceptions across five subscales: students’ perceptions of learning (SPL), students’ perceptions of teachers (SPT), students’ academic self-perception (SAP), students’ perceptions of atmosphere (SPA), and students’ social self-perception (SSP). One-way Analysis of Variance (ANOVA) with post hoc Tukey test was performed to compare mean scores between academic-programs and year-levels. Results The study’s response rate was 93.75%. Males constituted 16.36%, while females were 83.64%. The overall mean DREEM score was 144.35/200, indicating a generally positive EE. Medical students reported the highest mean score (147.43), followed by nursing (145.81) and pharmacy (136.70), with a significant difference between medical and pharmacy students. Year-3 students achieved significantly higher overall scores (148.54) and recorded the highest mean scores in SPL, SAP, and SSP compared to Year-2 students. Meanwhile, Year-1 students reported significantly higher scores in SPT and SPA than Year-2 students. Conclusion Students perceived the EE at WUC as more positive than negative. Program and year-specific issues highlight the need for faculty development. Faculty training and improved student support systems are recommended to strengthen students’ learning experience, and foster a more supportive EE. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 840-847